2003
DOI: 10.1111/j.1460-2466.2003.tb02592.x
|View full text |Cite
|
Sign up to set email alerts
|

An Asian Voice? A Comparative Study of Channel News Asia and CNN

Abstract: This study examined the claim that Asian journalism is essentially different from Western journalism through a comparative study of Channel News Asia (CNA), an international news channel operated by a Singapore company, and CNN. It analyzed the news bulletins aired by the 2 stations in their special news programs on Asia during 4 constructed weeks over a 6‐month period in 2000. The results show that despite its objective of presenting an Asian perspective in its newscasts, CNA is not significantly different fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 16 publications
(21 reference statements)
1
12
0
Order By: Relevance
“…The headlines and topics from each media outlet were categorized into one of 17 possible categories in an adapted codebook used previously in separate publications by Natarajan and Xiaoming [26] and Groshek [5]. The categories in these codebooks were: (1) Accidents/natural disasters, 2 As already noted, this study added a (17) Media category.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The headlines and topics from each media outlet were categorized into one of 17 possible categories in an adapted codebook used previously in separate publications by Natarajan and Xiaoming [26] and Groshek [5]. The categories in these codebooks were: (1) Accidents/natural disasters, 2 As already noted, this study added a (17) Media category.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Groshek examined the agendas of CNN and CNN International coverage online and found that though "there were differences in which issues were most salient on CNN and CNNI, the top three categories were the same for both: Crime, Politics, and War" [5]. Though previous research on professional intermedia agenda setting has generally found some important topical cleavages, evidence suggests that the overall and thematic differences are more subtle and becoming less distinct in what has become global media culture [25][26][27].…”
Section: Agenda Setting From Mass Media Through Social Mediamentioning
confidence: 99%
“…For the two British newspapers, coverage about the disasters occurring in China is by definition foreign coverage. In the literature of international communication, historically there is a common argument that foreign coverage is always about negative things (Galtung and Ruge, 1965; Goss, 2015; Natarajan and Hao, 2003; Riffe, 1993; Simon et al., 1989). A number of factors influence the production and selection of foreign news for coverage in media elsewhere in the world.…”
Section: The Case Studymentioning
confidence: 99%
“…Each story was coded into one of 16 possible categories that have been outlined in previous studies (Groshek, 2008;Natarajan & Xiaoming, 2003;Weaver, Porter & Evans, 1984): 1accidents/natural disasters, (2) agriculture, (3) business/economics, (4) crime/criminal justice/law and order, (5) ecology/environment, (6) education, (7) health care, (8) military/national defense,…”
Section: Codingmentioning
confidence: 99%